TANTANGAN DIPLOMASI BUDAYA: ANALISIS KONFLIK IDENTITAS NETIZEN INDONESIA-MALAYSIA DI MEDIA SOSIAL - Nirzila Erdawati; Naura Maharani; Putri Anggraini (JURNAL MULTIDISIPLIN ILMU AKADEMIK, 2026)
This study analyzes the challenges of Indonesia-Malaysia cultural diplomacy due to identity conflicts that have developed on social media. Although both countries share historical, cultural, and linguistic ties as kindred nations, their bilateral relations are often marked by tensions arising from cultural heritage disputes, migrant labor issues, and territorial conflicts. In the digital era, these conflicts have evolved into digital identity conflicts in the form of netwar and tauntwar between Indonesian and Malaysian netizens across various social media platforms. This study employs a qualitative approach with a case study method and qualitative content analysis techniques. Data were obtained through literature reviews sourced from scientific journals, international institution reports, policy documents, and relevant digital statistical data. The analysis was conducted using Joseph S. Nye's soft power theory as the main framework to understand the influence of digital identity conflicts on the effectiveness of cultural diplomacy. The findings reveal that digital identity conflicts pose a structural challenge to Indonesia-Malaysia cultural diplomacy, as negative narratives massively disseminated by non-state actors on social media are capable of eroding the positive image and public trust that serve as the primary foundation of soft power. These conflicts are reinforced by provocative media discourse construction, the spread of cyber-nationalism through digital networks, and low levels of public media literacy. This study concludes that the effectiveness of cultural diplomacy in the digital era requires a more adaptive public diplomacy strategy, the strengthening of cross-border digital literacy, and ASEAN involvement in managing digital identity conflicts to support regional socio-cultural integration.